E-Comic Improves Understanding of Indonesian Language Learning Results - Salsa Dika, Nazya; Kurniana Bektiningsih (MIMBAR PGSD Undiksha, 2023)
The problems currently occurring in elementary schools are limited variations in learning methods and students' difficulties in understanding spelling and the main idea of paragraphs. The aim of this research is to develop E-comics to improve understanding of Indonesian language learning outcomes. This type of research is development through 6 stages. This research involved research subjects consisting of media experts, material experts, and a group of fifth grade students consisting of 33 students. Data was collected through interviews, documentation and value assessments. The data collection instrument is a questionnaire. Data analysis techniques use descriptive qualitative, quantitative and inferential statistical analysis. The research results areThe e-comic media developed has gone through a careful evaluation and revision process and received high validation from media and material experts, exceeding the quality standard threshold. This media is considered appropriate and reliable to support learning and research. In addition, the results of the Wilcoxon test analysis show that there is a significant difference between pretest and post-test data, which shows an increase in students' understanding in the high category. It was concluded that E-comics can improve understanding of Indonesian language learning outcomes. This research is very relevant for advancing education and technology in using e-comics as a medium for learning Indonesian in elementary schools.